On the status and position of Melitaea minerva var. palamedes Groum-Grshimaïlo, 1890 (Lepidoptera: Nymphalidae) - S. K. Korb (SHILAP, 2017)
Melitaea palamedes Groum-Grshimaïlo, 1890 is treated here as a subspecies of M. minerva Staudinger, 1881, based on molecular data and morphology: Melitaea minerva  palamedes Groum-Grshimaïlo, 1890, stat. rev.